Critical Spots and Misconceptions in Students’ Understanding of Problems and Challenges in Europe - Škodová, Martina; Madleňák, Tibor; Mihoková, Michaela (European Journal of Geography, 2025)
Europe is currently undergoing dynamic change. European countries, regions, and populations face numerous economic, social, political, and environmental challenges. Reflection within the educational process plays a key role in understanding and responding to these developments. Teaching regional geography offers a suitable framework for such reflection. The regional geography of Europe holds strong potential for fostering understanding of diverse, complex, and often difficult issues. The aim of this study is to identify critical spots and common misconceptions in students’ understanding of problems and challenges in Europe. The study addresses the following research question. What critical spots and misconceptions appear in students’ understanding of European issues? The paper presents results from research focused on the most frequent misconceptions related to selected problematic topics in European geography. The research sample consisted of 304 students from selected secondary schools in Slovakia. Data were collected using a testing method applied after completion of a thematic unit on the regional geography of Europe. Statistical analysis conducted in RStudio confirmed the persistence of several misconceptions. These concerned perceptions of Russia, democracy, nuclear energy, and population ageing. For example, 89.1% of respondents did not perceive Russia as a country with a relatively high share of Muslims. In addition, 71.7% believed Switzerland has the highest level of democracy in Europe, without considering that Nordic countries often rank higher. Misconceptions also appeared in relation to nuclear energy, with 67.6% viewing nuclear power as highly environmentally unfriendly, and population ageing, where 57.9% believed ageing occurs more slowly in Southern Europe than in Northern Europe. Highlights: Teaching European issues should consider students’ key difficulties and misconceptions. Slovak students exhibit several misconceptions in the examined topics of the regional geography of Europe. The revealed misconceptions underline the need for contextualized and critical geography education.